“Trust Me, It’s Different”: Experiences of Peer Case Management of Women Living with HIV in Ontario, Canada - Greene, Saara; Ion, Allyson; Kwaramba, Gladys; Mwalwanda, Mary; Caswell, Janet; Guzha, Esther; Carvalhal, Adriana (Canadian Social Work Review / Revue canadienne de service social, 2015)
In response to the dearth of research for delivering women-centred support to women living with HIV, the Women’s HIV Empowerment Through Life Tools for Health (wHEALTH) intervention was developed. This project was grounded in a community-based research framework and aimed to respond to barriers of women living with HIV in accessing appropriate and meaningful social supports. Participants described the benefits of the peer case management intervention including support, mentorship, flexibility in which the intervention was delivered, and the notion of “moving forward” in one’s journey with HIV. Through education, awareness, and advocacy, peer case managers are important partners in addressing HIV-related stigma, and ensuring a multi-level approach to providing care and support to women living with HIV.